To proceed or not to proceed: ENT surgery in paediatric patients with acute upper respiratory tract infection. Issue 9 (25th July 2016) - Shemesh, S; Tamir, S; Goldfarb, A; Ezri, T; Roth, Y
Abstract: Background: Upper respiratory tract infection is the most common non-preventable cause of surgery cancellation. Consequently, surgeons and anaesthesiologists involved in elective ENT surgical procedures frequently face a dilemma of whether to proceed or to postpone surgery in affected children. Methods: A literature review was conducted and a practical assessment algorithm proposed. Conclusion: The risk–benefit assessment should take into consideration the impact of postponing the surgery intended to bring relief to the child and the risks of proceeding with general anaesthesia in an inflamed airway. The suggested algorithm for assessment may be a useful tool to support the decision of whether to proceed or to postpone surgery.